Bacterial Cross-contamination between clinic& dental laboratory during polishing procedure of complete denture (Mustansiria Dental Journal, 2018)
Polishing of dental prostheses can cause a dangerous cycle of cross-contaminationinvolving dentists, laboratory technicians, patients and auxiliary personnel. The aim ofthis study was to show the microbial contamination in the dental laboratory during thepolishing procedure of complete dentures. For this purpose, 30 samples & 4experiments were conducted.Experiment I - Determination of the contaminating complete maxillary denturesfrom plaque &from patient saliva .Experiment II- after disinfection of complete denturesExperiment III- determination of microorganism transferred During the polishingprocedure, to the dentureExperiment IV - The remaining microorganism in the lathe spindle Microbiologicaltests were conducted to detect the presence of bacteria. plates showing growth,colonies were observed and identified using Gram staining,. As a result viableorganisms from patients denture before and after polishing & after disinfectionwere found Improper disinfection of the denture , using tab water with pumicepowder allowed for the introduction of pathogens so The polishing of dentalprostheses is a possible source of transmission of communicable diseases in thelaboratory appropriate universal precautions must be followed to decrease thelikelihood of cross contamination